A Unique Presentation of Occult Primary Breast Cancer with a Review of the Literature. (18th March 2015) - Ahmed, Inaya; Dharmarajan, Kavita; Tiersten, Amy; Bleiweiss, Ira; Schmidt, Hank; Green, Sheryl; Bakst, Richard L.
Abstract : We are reporting a case of a 34-year-old woman with occult primary breast cancer discovered after initially presenting with neurological symptoms. She was successfully treated with neoadjuvant chemotherapy followed by definitive axillary lymph node dissection and ipsilateral whole breast radiotherapy. The case presented is unique due to the rarity of occult primary breast cancer, especially in light of her initial confounding neurological signs and symptoms, which highlights the importance of careful staging.